(3GdRgO hGdQbGFbs - (3YHO Gddg Hf GdeHGQc Hf hGVM GdMfXdj HGdhdGA GdJejej GdeQhRj, CHh YHO GdQMef,J (B181 (3g` s
(3ChdgG (B:s
(3HGH GdJQZjH ai GdeHGOQI HGdYed MOKfG CHh HcQ eMeO Hf ESMGb bGd (B: (3bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3fYeJGf eZHhf ajgeG cKjQ ef GdfGS GdUMI hGdaQGZ s
(3BNQgG (B:s
(3Yf YHO Gddg Hf eSYhO bGd (B: (3JSGQYhG Edi GdLeYI aEf Gddg JHGQc hJYGdi jHQR dCgd GdLfI ai cd jhe LeYI Je GdLRA GdSGOS YTQ hgh BNQ cJH GdQbGFb s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B115s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdMOjK h GdeUWdMs